CONSUMER TRUST: A DECISIVE FACTOR OF ONLINE SHOPPING (INTERNATIONAL SEMINAR, 2024)
In the midst of rapid e-commerce platform growth, building trust has become a critical challenge for companies to attract and retain customers. This research aims to identify and analyze the factors that shape consumer trust, encompassing ability, benevolence, and integrity, and how these three factors contribute to purchase decisions. Research data was collected through a Likert-scale questionnaire, distributed to 100 active Shopee users aged 18–35 years. This age group was selected because they represent the most active generation in online shopping, namely Generation Z and Millennials. Data analysis was conducted using a descriptive approach with SPSS software. Research findings reveal that platform reputation, user reviews, and transaction security guarantees play a key role in building consumer trust levels. These factors not only enhance consumer confidence in the platform but also drive customer loyalty through safe, convenient, and satisfying shopping experiences. The findings of this research provide significant theoretical and practical contributions. Theoretically, this study expands the understanding of consumer trust dynamics in the e-commerce context. Practically, these results can serve as a reference for e-commerce companies in designing marketing strategies focused on improving consumer trust. By prioritizing elements such as delivery reliability, product information transparency, and transaction security guarantees, companies can create a trustworthy shopping environment that attracts more customers, ultimately contributing to long-term business success